The identification of genomic regions associated with tick count, growth traits, and skin thickness in F2 angus x Nguni cattle using genome-wide association analysis - Mkize, Nelisiwe (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhDAgric)--Stellenbosch University, 2023.